Business model analysis of natural production forest with sustainable forest management approach - Mohammad Noer; Saribanon, Nonon; Nurwulandari, Andini (Penerbit Universiti Kebangsaan Malaysia, 2017)
Deforestation and conversion of forest land in Indonesia continues. Data show that within 12 years there has been a decline in forest area in Indonesia amounted to approximately 20 million hectares, or an average of 1.7 million hectares per year. Other data show that between 1990-2010, Indonesia forest area shrank from 118 million hectares to 94 million hectares in 2010, whether caused by changes in the function of forest, forest fires, or unsustainable forest management, with the deforestation rates 450,637.1 ha/year. Sustainale forest management has been known to be effective in absorbing carbon emissions through increased in-growth and productivity of natural forests, and maintain its biodiversity and environmental functions. Currently a decline in production of natural forest area, which is caused by various factors such as a poor investment climate. The research method is based on qualitative research, ie in-depth interviews, Focus Group Discussion (FGD), SWOT Analysis, and Business Model Canvas (BMC). Result of the research shown that: 1) Business Model Canvas date suggests that customers Kaltim forest resources consist of domestic and foreign companies, universities, foreign tourists and domestik. Service to customers who want environmentally friendly wood enhanced by selling certified wood; (2) The results of a SWOT analysis indicates the certainty area (land dispute), the low to the high Law enforcement of illegal logging, not an institutional one door, timber prices are low, holder IUPHHK make messy collapse of the forest industry; (3) The Strategy of Sustainable Forest Management (SFM) through BMC improved is the element key partnership in the form of governance of institutional fixed, protecting customary rights, provide incentives for IUPHHK, while the element Key activity in the form of certified HR forestry, and the elements of Customer segement is a green marketing strategy.